Identificação, caracterização e controle in vitro de Phoma pedeiae (Aveskamp, Gruyter & Verkley) associado à Cedrela fissilis Vell. - Dutra, Adriana Falcão (2018)
The species Cedrela fissilis Vell. (cedro) presents good growth, producing wood of excellent quality, causing intense exploitation by the loggers. One of the main problems that compromise the production of wood is the occurrence of pests and diseases, causing serious damages to the host and changes in the physiological processes, leading to the death of the plant. Thus, the study of the biological activity of essential oils (OEs) of plants can constitute a potential form of control of diseases in plants. The objective of this study was the identification and morphological and molecular characterization of Phoma spp. associated with Cedrela fissilis Vell., and to evaluate the antifungal activity of cedro OE in the in vitro control of Phoma pedeiae. Leaflets were collected from adult trees with symptoms of the disease (Santa Maria, RS) and sent to the Elocy Minussi Phytopathology Laboratory (UFSM) for isolation of the fungus. The material was observed on stereoscopic and optical microscopes, and when fungal structures were present, they were transferred to Petri dishes containing BDA. After 14 days of development, the fungus was purified by monosporic culture and transferred to the BDA, CA and V8 media for morphological and molecular characterization. The pathogenicity of the fungus was performed by sprinkling on leaves for two isolates. The morphological characteristics analyzed were: mycelial growth (MG), mycelial growth rate (MGR) and growth rate index (GRI), sporulation, colony pigmentation and conidia characterization. OE extraction was carried out in the Laboratory of Extractive Plants, and OE was extracted from young cedro leaflets, in the spring season of 2015, 2016 and 2017, by hydrodistillation. The in vitro antifungal activity of leaflets OE was on pure colonies of Phoma pedeiae, at concentrations of 0.5, 0.75, 1.0 and 1.5 μL mL-1, in addition to positive and negative controls. Daily measurements of the colony diameter were carried out for 14 days, with MG, MGR, GRI and inhibition of mycelial growth. Sequences were deposited in GenBank and 70 and 81% similarly, with the fungus Didymella pedeiae, sexual form of Phoma pedeiae, by means of the sequencing of genes from the ITS and β-tubulin regions. The symptoms caused by the fungus started at 20 days after inoculation, not differing between the two isolates, causing the death of the individuals in 50 days. The fungus presented rounded pycnidia of black coloration, white mycelium and oblong oval conidia, without septum and hyaline. Sporulation in the V8 culture medium was superior to the BDA and CA medium. At the end of the three-year evaluation, 45 OE components of cedar leaflets were identified, corresponding to approximately 90% of the total OE composition, with the predominance of β-caryophyllene, spathulenol and caryophyllene oxide. The cedro OE presented relative antifungal activity against P. pedeiae starting at the concentration of 0.5 μL mL-1. There fore, it can be indicated for use in the control of pathogens, because it is a secondary metabolite, not causing damage to the environment.